Developing Problem-Based Learning Flipbook Media to Enhance Natural Sciences Education in Fifth Grade - Rosli Fadhilah; Petra Kristi Mulyani (Postgraduate, University of Mataram, 2024)
The lack of diverse learning media was a factor that impacted student understanding, resulting in low learning outcomes. This study aimed to develop a problem-based learning (PBL) flipbook on environmental damage content as a media for science education in fifth-grade elementary. The research utilized the ADDIE model. The study used two classes: one experimental class with 22 students and one control class with 20 students. Data collection instruments included questionnaires and tests. The results indicated that the PBL flipbook media was highly suitable and effective for supporting science learning in fifth grade. Media experts validated the flipbook and rated it in the qualified category with a score of 93%, meaning that the media emphasizes presentation according to the target; the supporting presentation was interesting; the learning presentation was appropriate; the language used was appropriate; and the cover design and content were interesting. Content experts validated the flipbook and rated it in the very suitable category with a score of 91%, which means that the content was presented following the learning objectives; the content was presented appropriately; there were appropriate presentation supporters; the language used was appropriate and the level of language was appropriate for students; and appropriate learning syntax. The average user response was 91%, meaning that the flipbook content was presented appropriately; the flipbook was easy to use; the language level was appropriate, the flipbook was interesting; the flipbook was useful; and the learning steps were appropriate. The effectiveness of PBL-based flipbooks in improving students' understanding of the content was indicated by the results of the Sig (2-tailed) 0.01 t-test, meaning that there were significant differences in learning outcomes between experimental and control classes after treatment.